Near infrared hyperspectral imaging and chemometrics for exploration and classification of whole wheat kernels - Du Toit, Gerida (Stellenbosch : University of Stellenbosch, 2009)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2009.